Melihat Peluang Bisnis dan Usaha dengan Critical Thinking Ability oleh Mahasiswa IAIN Takengon - Harnedi, Joni; Sari, Rahmahidayati (Lembaga Yasin AlSys, 2024)
This research is motivated by the importance of critical thinking skills in seeing business and business opportunities, especially for students of sharia economics and sharia banking study programs/departments to support business opportunities and businesses that they are currently running and will be running. This research aims to analyze the ability to see business and business opportunities of Sharia economics and Sharia banking students using critical thinking skills. This research uses descriptive mixing method. Data was collected by randomly distributing Likert scale questionnaires and interview to 50 respondents from Sharia economics and sharia banking study program students. Percentage statistics are used to provide a clear picture of data distribution. Research findings show that the critical thinking possessed by respondents is generally in the sufficient category when looking at business and business opportunities. Respondents have sufficient systematic thinking skills, have sufficient business instincts to start a business, are able to consider various solutions quite well, consider implications and identify problems and potential solutions quite well, but due to limited energy, time and funds, sometimes business what they do is like suspended animation. This research is significant in providing an understanding of the ability of business opportunities by using the critical thinking skills that are requested and required and trained in formal education carried out by students.